Environmental Management in the Capital city of Luang Prabang, Luang Prabang Province with a Public’s Participative Process Case study: The People of 10 Pillages in the Capital city of Luang Prabang - HOUNGPASERTH, Sisouphan; CHANSAVANG, Bounsana; BOUNSAIYAVONG, Somsanook; SITTIVONG, Phoutthamala; SIMMAVONG, Konsaeng (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
This study aimed to survey the environmental management, study the level of public participation towards environmental management, as well as the guidelines of environmental solutions in the capital city of Luang Prabang, Luang Prabang province. The study was conducted with the samples of population from 10 villages in the capital city of Luang Prabang municipality; the number of 390 samples was selected by the proportion of the population and the simple random sampling method. The data collection was through a five-rating scale questionnaire with analytical statistics by using frequency, percentage, average, and standard deviation. The study was found that the environmental management in the area was overall at a moderate level. When considered in each aspect, the average value of Mean scores was ranked from the most to the least accordingly: Control of Management Action, Sustainable Handling, and Disposal Treatment of Waste/Pollution, respectively. The public’s participation towards the environment management was overall at a moderate level. When considered in each aspect, the average value of Mean scores was ranked from the most to the least accordingly: Participation in Monitoring and Evaluation of Development Plans and Projects, Participation in Interest of Development, Participation in the Implementation of Development Plans and Projects, and Participation in Decision-Making. The comparison analysis of public’s participation in the area towards the environmental management upon sex, age, education, occupation, and length of residence in the area was different in terms of Sustainable Handling, Disposal Treatment of Waste/Pollution, and Control of Management Action, except for Participation in Decision-Making, Participation in Monitoring and Evaluation of Development Plans and Projects, Participation in the Implementation of Development Plans and Projects, and Participation in Interest of Development. For suggestions, it was indicated that people from all sectors would participate in thinking, doing, monitoring and evaluating the municipal’s acting performance so that the managerial performance would be effective, transparent, and accountable. Besides, the public or stakeholders would be encouraged to get an opportunity to suggest their opinions and participate in any activities to enhance their quality of living in the area as well as to raise their self-awareness about the efficacy of the municipal’s acting performance. This could bring about a sustainable development of its environmental management in the coming years.